[Dorm mailboxes] (1969)
Above the mailboxes, there is a sign that reads 'Mail is in,' and a poster that reads 'Mustang Band presents 2nd annual Band O Rama, Friday November 1, 1968, Cal Poly Little Theater.' A bulletin board is situated between the mailboxes and has posters hanging on it.